Clinico-epidemiological profile of molar pregnancies in a tertiary care centre of Eastern Nepal: a retrospective review of medical records. Issue 1 (May 2015) - Agrawal, Nimisha; Sagtani, Reshu; Budhathoki, Shyam; Pokharel, Hanoon
Abstract Background The incidence of molar pregnancy has demonstrated marked geographic and ethnic differences. The reported data in Nepal is inconsistent with minimal published literature. Thus, we designed a study to determine prevalence of molar pregnancies and demonstrate clinical and epidemiological characteristics of the patients attending a tertiary care center in eastern Nepal. Methods A retrospective review of medical records was conducted to determine the prevalence of molar pregnancies at the B.P. Koirala Institute of Health Sciences (BPKIHS) from the year 2008 to 2012. Secondary data from the medical records were analyzed. Annual and 5-year prevalence of molar pregnancy per 1000 live births was calculated. Demographic characteristics, clinical presentation, management methods and complications of molar pregnancy were studied. Results The 5- year prevalence of molar pregnancy at BPKIHS is 4.17 per 1000 live births with annual prevalence ranging 3.8–4.5 per 1000 live births. More than one third of the patients were in the age group of 20–35 years and majority of them were of Hindu religion. For more than one third (41.7 %) of the patients, it was their first pregnancy while about 10 % gave a positive past history of molar pregnancy. Abnormal uterine bleeding (86.3 %) was the most frequent complaint, suction evacuation was the most common method of treatment and more than half of the patients required prolonged care after initial management. Conclusion There is a need for studies at country level which will give us a national figure on molar pregnancies. Thus, a standardized clinic-epidemiological profile of molar pregnancy in Nepal can be created.